Doenças diagnosticadas em aves silvestres e exóticas no setor de patologia da Escola de Veterinária da Universidade Federal de Minas Gerais no período de 2006 a 2021 - Maira dos Santos Carneiro Lacerda (2022)
Free-living wild and exotic birds, as well as captive and apprehended avian are prone to develop diseases of multiple etiologies according to the environment in which they are inserted. The aim of this work is to determine the diseases and to evaluate the frequency in wild and exotic birds, correlating it with their respective source (private captivity, free-living or apprehension). Data from birds sent to the Setor de Patologia Veterinária da Escola de Veterinária (EV) of the Universidade Federal de Minas Gerais (UFMG) were compiled between the period of 2006- 2021 (retrospective and prospective study). During the retrospective study (2006-2019), anatomopathological reports were retrieved from birds that fit into the categories mentioned above. Histochemical and immunohistochemical techniques, as well as molecular tests (Polymerase Chain Reaction), sequencing, and phylogenetic analysis were performed as available to assist in the histopathological diagnosis. A total of 240 birds were obtained during this study, among which 23.33% were from exotic birds, and 76.66% were from wild birds. Of the total number of birds, 37.5% were obtained from the apprehension of illegal bird trades. The most frequent primary infectious diseases were parrot Herpesvirus (8.75%) in birds obtained from illegal trade; followed by Aspergillus spp. (6.25%), found mostly in captive birds; and Chlamydia psittaci (5%), in illegally trafficked birds. Hepatic lipidosis and uric gout were the most frequent conditions among the metabolic diseases, with 33,33% and 2.91% of cases, respectively, without major differences between the source of the birds. Co-infections were also observed, and the association between viruses and bacteria were the most common type of association, with 4.5% of cases occurring in free-living birds apprehended from illegal traffic. Infectious diseases were the most frequent diseases in both captive and illegally trafficked free-living birds, while co-infections were more common in captive birds. Histochemical, immunohistochemical and molecular techniques were essential for the definitive diagnosis of most of the diseases found in this study.